Evolution of BDNF serum levels during the first six months after alcohol withdrawal. (25th November 2020) - Girard, Murielle; Labrunie, Anaïs; Malauzat, Dominique; Nubukpo, Philippe
Abstract: Objectives: Brain-Derived Neurotrophic Factor (BDNF) has been associated with alcohol dependence and appear to vary after withdrawal, although the link with the withdrawal outcome on the long term is unknown. We aimed to assess the evolution of BDNF levels during the six months following withdrawal and determine the association with the status of alcohol consumption. Methods: Serum BDNF levels of alcohol-dependent patients ( n  = 248) and biological and clinical parameters were determined at the time of alcohol cessation (D0), 14 days (D14), 28 days (D28), and 2, 4, and 6 months after (M2, M4, M6). Results: Abstinence decreased during follow-up and was 31.9% after six months. BDNF levels increased by 14 days after withdrawal and remained elevated throughout the six-month period, independently of alcohol consumption. Serum BDNF levels evolved over time ( p  < 0.0001), with a correlation between BDNF and GGT levels. The prescription of baclofen at the time of withdrawal was associated with higher serum BDNF levels throughout the follow-up and that of anti-inflammatory drugs with lower BDNF levels. Conclusions: A link between BDNF levels, liver function, and the inflammatory state in the context of alcohol abuse and not only with alcohol dependence itself is proposed.